NIAGADS: The NIA Genetics of Alzheimer's Disease Data Storage Site. Issue 11 (23rd September 2016) - Kuzma, Amanda; Valladares, Otto; Cweibel, Rebecca; Greenfest‐Allen, Emily; Childress, Daniel M.; Malamon, John; Gangadharan, Prabhakaran; Zhao, Yi; Qu, Liming; Leung, Yuk Yee; Naj, Adam C.; Stoeckert, Christian J.; et al.
Summary: Work in the past 10 years has greatly expanded our understanding of Alzheimer's disease (AD) genetics, with more than 20 susceptibility genetic loci discovered in large genome‐wide association and sequencing studies. The NIA Genetics of Alzheimer's Disease Data Storage Site (NIAGADS) is funded by National Institute on Aging to serve as a one‐stop portal for the community to access research data and findings generated from AD genetics projects. In this article, we describe the mission of NIAGADS, available resources, and data sets including the Alzheimer's Disease Sequencing Project, and how researchers may apply for access to genetic data.